2016
DOI: 10.1016/j.jad.2015.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of complex negative emotions induced by music in euthymic patients with bipolar disorder

Abstract: a b s t r a c tBackground: Research has shown bipolar disorder to be characterized by dysregulation of emotion processing, including biases in facial expression recognition that is most prevalent during depressive and manic states. Very few studies have examined induced emotions when patients are in a euthymic phase, and there has been no research on complex emotions. We therefore set out to test emotional hyperreactivity in response to musical excerpts inducing complex emotions in bipolar disorder during euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…One study looking at the effects of music therapy on bipolar disorder patients in a euthymic (normal mood) state found that music created more complex negative emotions in those responding to subjectively uplifting music (Choppin et al, 2016). Data was collected from participants using two self-reported scales (ERS and MAThyS), along with scales that required them to rate their music-induced emotions.…”
Section: Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…One study looking at the effects of music therapy on bipolar disorder patients in a euthymic (normal mood) state found that music created more complex negative emotions in those responding to subjectively uplifting music (Choppin et al, 2016). Data was collected from participants using two self-reported scales (ERS and MAThyS), along with scales that required them to rate their music-induced emotions.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…One hypothesis for these results was that patients with bipolar disorder might respond in this way as a result of their struggle to regulate their own positive emotions, which creates a form of distress manifested as a negative emotion. While the data says little for the effectiveness of music listening alone on bipolar disorder, the research group posited that listening to music could be a beneficial tool in allowing patients to better understand their emotions and the roots therein (Choppin et al, 2016).…”
Section: Bipolar Disordermentioning
confidence: 99%
“…The stimuli consisted of 12 excerpts of instrumental music from the previous four centuries, taken from commercially available CDs (See Supplementary material, Table 1). This set of stimuli was derived from a previous study (Trost et al, 2012) and had already been used in the same format in another study (Choppin et al, 2016). The choice of excerpts avoided extremely popular pieces from the classical music repertoire, in order to reduce potential biases stemming from memory and semantic knowledge associated with the music.…”
Section: Musical Stimulimentioning
confidence: 99%
“…More recently, the GEMS has also been studied in a clinical context. When Choppin et al (2016) investigated emotional alterations in patients with bipolar disorder in response to music, they found that patients in a euthymic state experienced music inducing wonder as more negative than controls did (Choppin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Neurofeedback is a noninvasive self-training regimen that improves brain function in the prefrontal cortex, cingulate cortex (4) by inducing specific changes on waves (EEG) (5,6). During NeurOptimal® training (NO), all participants are listening a new age piece music (the same for all of them) given its beneficial effect on physiological parameters (7)(8)(9)(10)(11). NeurOptimal® use "music interruptions" to generate changes on brain activity (www.zengar.com, Zengar Institute, Canada).…”
Section: Introductionmentioning
confidence: 99%